STUDY THE EFFECT OF ERROSION ON THE BREAKAGE OF STEAM TURBINE BLADE AT BAIJI POWER STATION - Mohaned A. Daher (Tikrit Journal of Engineering Sciences, 2013)
The last stage endured on obvious erosion especially the front and the end of the blade. The erosion caused the appearance some cracks in this place. These remarks coincided with the theoretic   al results, which were acquired according to the condition of the turbine of station which showed that the droplet, which collided with the blade ends, caused high pressure on the surface of the blade and caused the occurrence of the corrosion. The danger of the erosion unavoidable due to its relationship with tae station efficiency and the only to avoid that is the use of the blade made of erosion resistance ingots.